Digital migration barriers: Exploring disadvantages faced by low-skilled migrants in an era of rapid digitalization - Morales, Ysabell D. (Animo Repository, 2024)
This paper investigates the impact of e-government services and automation on low-skilled Filipino migrants to Italy. The rapid digitalization in the Philippines has added complexities to the migration journey, especially for those from sectors vulnerable to automation. This research explores how these digital transformations heighten challenges for migrants, emphasizing the need for inclusive strategies to navigate the evolving migration landscape. The study focuses on the impact of automation and pre-departure e-government services, highlighting the socio-economic gaps that they create. By examining the migration experiences of low-skilled Filipino workers in Italy, the research aims to provide insights into the interplay between technological advancements and migration dynamics, addressing the critical need for equitable access and support in a digitalized world.